Potent Antiviral Activity of Topoisomerase I and II Inhibitors against Kaposi's Sarcoma-Associated Herpesvirus - González-Molleda, Lorenzo (American Society for Microbiology, 2012)
The lytic DNA replication of Kaposi's sarcoma-associated herpesvirus (KSHV) initiates at an origin (ori-Lyt) and requires trans-acting elements, both viral and cellular. We recently demonstrated that several host cellular proteins, including topoisomerases I and II (Topo I and II), are involved in KSHV lytic DNA replication (Y. Wang, H. Li, Q. Tang, G. G. Maul, and Y. Yuan. J. Virol. 82: 2867–2882, 2008). To assess the importance of these topoisomerases in viral lytic replication, shRNA-mediated gene silencing was used. Depletion of Topo I and II severely inhibited viral lytic DNA replication as well as virion production, suggesting essential roles of these cellular proteins in viral DNA replication. The discovery of Topo I and II as enzymes indispensable for KSHV DNA replication raises a possibility that these cellular proteins could be new targets of therapeutic approaches to halt KSHV replication and treat KSHV-associated diseases. In this report, we examined one Topo I inhibitor and several Topo II inhibitors (inclusive of Topo II poison and catalytic inhibitors) as potential therapeutic agents for blocking KSHV replication. The Topo II catalytic inhibitors in general exhibited marked inhibition on KSHV replication and minimal cytotoxicity. In particular, novobiocin, with the best selectivity index (SI = 31.62) among the inhibitors tested in this study, is effective in inhibiting KSHV DNA replication and virion production but shows little adverse effect on cell proliferation and cycle progression in its therapeutic concentration, suggesting its potential to become an effective and safe drug for the treatment of human diseases associated with KSHV infection.